Inventory management over firm life cycle: some empirical evidence. (5th November 2014) - Elsayed, Khaled
Despite managing inventory being considered an essential function in production and operations management discipline, prior research has revealed contested conclusions regarding its determinants. In fact, the impact of collective dynamic change in firm characteristics on inventory performance and how such dynamic change can lead to a non-proportional inventory performance, have not been examined in literature. An alternative approach that this study proposes in examining the inventory performance is that it might depend on the firm's life cycle stage. Econometric analysis, using a sample of 84 Egyptian listed firms between 2005 and 2010, gives substantial support for the proposed argument. Explicitly, the findings strongly suggest that firms in the expansion stage have a better inventory performance than firms in either the inception stage or the maturity stage. The results also demonstrate that firms in the revival stage have a better inventory performance than firms in the maturity stage. It is believed that this novel theoretical and empirical evidence has significant implications for understanding of the inventory literature.